Prospective study of DNA methylation at LINE‐1 and Alu in peripheral blood and the risk of prostate cancer. Issue 15 (7th August 2015) - Barry, Kathryn Hughes; Moore, Lee E.; Liao, Linda M.; Huang, Wen‐Yi; Andreotti, Gabriella; Poulin, Matthew; Berndt, Sonja I.
<x xml:space="preserve">Abstract</x> BACKGROUND Evidence suggests that global blood DNA methylation levels may be associated with the risk of various cancers, but no studies have evaluated this relationship for prostate cancer. METHODS We used pyrosequencing to quantify DNA methylation levels at the long interspersed nuclear element 1 (LINE‐1) and Alu repetitive elements in pre‐diagnostic blood samples from 694 prostate cancer cases and 703 controls from the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial. We evaluated prostate cancer risk associated with the mean methylation level for each element using logistic regression, adjusting for potential confounders. RESULTS We did not observe a significant association with prostate cancer for LINE‐1 [odds ratio (OR) for the highest compared to the lowest quartile = 1.01, 95% confidence interval (CI): 0.73–1.39, Ptrend = 0.99] or Alu (OR = 0.94, 95% CI: 0.68–1.29, Ptrend = 0.69) methylation levels overall. However, for Alu, we observed that higher DNA methylation levels were associated with a significant increased risk for those diagnosed 4 or more years after blood draw (OR = 2.26, 95% CI: 1.27–4.00, Ptrend = 4.4 × 10−3). In contrast, there was no association for those diagnosed 2 (OR = 1.13, 95% CI: 0.67–1.90, Ptrend = 0.64) or 3 years after draw (OR = 1.22, 95% CI: 0.71–2.07, Ptrend = 0.32), and a decreased risk for those diagnosed less than 2 years after draw (OR = 0.40, 95% CI: 0.25–0.65, Ptrend = 3.8 × 10−5; Pheterogeneity = 5.3 × 10−6). CONCLUSIONS Although LINE‐1 DNA methylation levels were not associated with prostate cancer, we observed an association for Alu that varied by time from blood draw to diagnosis. Our study suggests that elevated Alu blood DNA methylation levels several years before diagnosis may be associated with an increased prostate cancer risk. Prostate 75:1718–1725, 2015. © 2015 Wiley Periodicals, Inc.